1974
DOI: 10.1084/jem.139.3.560
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Mediated Immunity Against Besnoitia and Toxoplasma in Specifically and Cross-Immunized Hamsters and in Cultures

Abstract: The capacity of hamster peritoneal cell populations to control viability and growth of Besnoitia and Toxoplasma organisms was assessed in vivo and in vitro. Immunized hamsters reduced the homologous organisms 100- to 10,000-fold over a 5-day period, but the heterologous infection increased 100- to 1,000-fold in numbers, similar as in the nonimmune controls. Passively administered antibody was ineffective although lytic cofactors were supplied by hamsters. In cultures, peritoneal cells from Besno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
31
1

Year Published

1974
1974
1986
1986

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 37 publications
(23 reference statements)
4
31
1
Order By: Relevance
“…However, the mechanism whereby the cells acquire the enhanced ability to inhibit or kill this parasite is still unclear . Several studies with experimental animal and human models have shown that nonimmune macrophages cocultured with lymphocytes from Toxoplasma-immune hosts and specific antigen can acquire anti-Toxoplasma activity (9,22). Based on these findings, a number of attempts have been made to induce anti-Toxoplasma activity within nonimmune macrophages or human monocytes by incubation with supernatants obtained from specifically stimulated immune lymphocytes (2,4,21,22).…”
mentioning
confidence: 99%
“…However, the mechanism whereby the cells acquire the enhanced ability to inhibit or kill this parasite is still unclear . Several studies with experimental animal and human models have shown that nonimmune macrophages cocultured with lymphocytes from Toxoplasma-immune hosts and specific antigen can acquire anti-Toxoplasma activity (9,22). Based on these findings, a number of attempts have been made to induce anti-Toxoplasma activity within nonimmune macrophages or human monocytes by incubation with supernatants obtained from specifically stimulated immune lymphocytes (2,4,21,22).…”
mentioning
confidence: 99%
“…This applies equally well to L. monocytogenes as to T . gondii infections (10,14,21,24). The ultimate killer cells in these infections are the activated macrophages (20,23,25,34).…”
Section: Discussionmentioning
confidence: 99%
“…Humoral antibody by itself is not considered to be of primary importance (Lindberg and Frenkel, 1977) because cell-mediated mechanisms have been shown to play the principal role in uitro (Remington, Krahenbuhl and Mendenhall, 1972;Borges and Johnson, 1975;Jones, Len and Hirsch, 1975), and in uiuo (Frenkel, 1967;Hoff and Frenkel, 1974). Furthermore, the thymus plays an essential part in the development of immunity to T. gondii (Hof et al, 1976;Buxton, 1980).…”
Section: Discussionmentioning
confidence: 99%